- #1
techmologist
- 306
- 12
I am trying to find a simple proof for the apparently simple formula
(x or x) implies x
using the axiom system of Lukasiewics. This axiom system uses only -> (implies) and ~ (not) as its primitive connectives. "x or y" stands for the formula ~x -> y.
A1) x -> (y -> x)
A2) (x -> (y -> z)) -> ( (x -> y) -> (x -> z) )
A3) (~x -> ~y) -> (y -> x)
Along with these are the usual rules of inference: modus ponens and substitution of formulas for variables.
The first few theorems that follow are:
T1) x -> x
T2) (y -> z) -> ( (x -> y) -> (x -> z) )
T3) ~x -> (x -> y)
T4) ~~x -> x
T5) x -> ~~x
T6) (~x -> y) -> (~y -> x)
T7) x -> ( (x -> y) -> y)
T8) (x -> (y -> z) ) -> (y -> (x -> z) )
T9) (x -> y) -> ( (y -> z) -> (x -> z) )
I'm trying to prove (x or x) -> x, which stands for (~x -> x) -> x
Here is a sketch of the proof I found:
(1) x -> ( (~x -> x) -> x).....A1
(2) ~x ->( (~x -> x) -> x)......T7
or letting a stand for ( (~x ->x) -> x)
(1') x -> a
(2') ~x -> a
(3) ~a -> x..........T6, etc. (omitting appeals to Modus Ponens and more obvious rules)
(4) ~a -> a..........(1'), (3), T2, ...
(5) (a -> (~a -> ~y) ) -> (~a -> (~a -> ~y) )...T9, ...
(6) (~a -> (a -> ~y) ) -> (a -> (~a -> ~y) )...T8
(7) (~a -> (~a -> ~y) ).......(5), (6), T2, T3 ...
(8) (~a ->~a) -> (~a -> ~y) ).......A2,...
(9) (~a -> ~y) )..........T1,...
(10) y -> a............A3,...
(11) (z -> z) -> a.........Substitution
(12) a............T1
That's just a sketch, not listing all the steps. Is there a shorter way to prove this innocuous looking theorem?
(x or x) implies x
using the axiom system of Lukasiewics. This axiom system uses only -> (implies) and ~ (not) as its primitive connectives. "x or y" stands for the formula ~x -> y.
A1) x -> (y -> x)
A2) (x -> (y -> z)) -> ( (x -> y) -> (x -> z) )
A3) (~x -> ~y) -> (y -> x)
Along with these are the usual rules of inference: modus ponens and substitution of formulas for variables.
The first few theorems that follow are:
T1) x -> x
T2) (y -> z) -> ( (x -> y) -> (x -> z) )
T3) ~x -> (x -> y)
T4) ~~x -> x
T5) x -> ~~x
T6) (~x -> y) -> (~y -> x)
T7) x -> ( (x -> y) -> y)
T8) (x -> (y -> z) ) -> (y -> (x -> z) )
T9) (x -> y) -> ( (y -> z) -> (x -> z) )
I'm trying to prove (x or x) -> x, which stands for (~x -> x) -> x
Here is a sketch of the proof I found:
(1) x -> ( (~x -> x) -> x).....A1
(2) ~x ->( (~x -> x) -> x)......T7
or letting a stand for ( (~x ->x) -> x)
(1') x -> a
(2') ~x -> a
(3) ~a -> x..........T6, etc. (omitting appeals to Modus Ponens and more obvious rules)
(4) ~a -> a..........(1'), (3), T2, ...
(5) (a -> (~a -> ~y) ) -> (~a -> (~a -> ~y) )...T9, ...
(6) (~a -> (a -> ~y) ) -> (a -> (~a -> ~y) )...T8
(7) (~a -> (~a -> ~y) ).......(5), (6), T2, T3 ...
(8) (~a ->~a) -> (~a -> ~y) ).......A2,...
(9) (~a -> ~y) )..........T1,...
(10) y -> a............A3,...
(11) (z -> z) -> a.........Substitution
(12) a............T1
That's just a sketch, not listing all the steps. Is there a shorter way to prove this innocuous looking theorem?